Molecular detection of piroplasmids in mammals from the Superorder Xenarthra in Brazil - Calchi, Ana Cláudia [UNESP]; Yogui, Débora Regina; Alves, Mario Henrique; Desbiez, Arnaud Leonard Jean; Kluyber, Danilo; Vultão, Juliana Gaboardi; Arantes, Paulo Vitor Cadina [UNESP]; de Santi, Mariele [UNESP]; Werther, Karin [UNESP]; Teixeira, Marta Maria Geraldes; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Springer Nature, 2023)
Xenarthra mammals can be found from southern North America to southern South America, including all Brazilian biomes. Although it has been shown that Xenarthra mammals can play a role as reservoirs for several zoonotic agents, few studies investigate the diversity of piroplasmids (Apicomplexa: Piroplasmida) in this group of mammals. Taking into account that piroplasmids can cause disease in animals and humans, understanding the prevalence and diversity of piroplasmids in Xenarthra mammals would contribute to conservation efforts for this group of animals as well as to infer risk areas for transmission of emergent zoonosis. The present study aimed to investigate the occurrence and molecular identity of piroplasmids in free-living mammals of the Superorder Xenarthra from four Brazilian states (Mato Grosso do Sul, São Paulo, Rondônia, and Pará). For this, DNA was extracted from blood or spleen samples from 455 animals. A nested PCR based on the 18S rRNA gene was used as screening for piroplasmids. Of the 455 samples analyzed, 25 (5.5%) were positive. Additionally, PCR assays based on 18S rRNA near-complete, cox-1, cox-3, hsp70, cytB, β-tubulin genes and the ITS-1 intergenic region were performed. Five out of 25 positive samples also tested positive for ITS-1-based PCR. The phylogenetic analysis positioned three 18S rRNA sequences detected in Priodontes maximus into the same clade of Babesia sp. detected in marsupials (Didelphis albiventris, Didelphis marsupialis, and Monodelphis domestica) and Amblyomma dubitatum collected from opossums and coatis in Brazil. On the other hand, the 18S rRNA sequence obtained from Dasypus novemcinctus was closely related to a Theileria sp. sequence previously detected in armadillos from Mato Grosso State, grouping in a subclade within the Theileria sensu stricto clade. In the phylogenetic analysis based on the ITS-1 region, the sequences obtained from Myrmecophaga tridactyla and Tamandua tetradactyla were placed into a single clade, apart from the other piroplasmid clades. The present study demonstrated the molecular occurrence of Piroplasmida in anteaters and Babesia sp. and Theileria sp. in armadillos from Brazil.
Keywords: Anteaters; Armadillos; Piroplasmids; Sloths